Experiment on Strength and Failure Behavior of Sandstone Containing Pre-Existing Cracks Under Brazilian Compression - Cao, Xiaojian; Zhang, Han; Yu, Jun; Yu, Tianchong; Qing, Yuxing (Frontiers in Physics, 2021)
Determination of the mechanical properties of rock containing pre-existing cracks under tension condition is of great significance to understand the failure process of rock in engineering. This paper presents the experimental results of sandstone containing pre-existing cracks under Brazilian compression. The characteristics of the microcracks were analyzed by a scanning electron microscope. The results show that the rock containing pre-existing cracks has an obvious anisotropic characteristic. When the crack inclination is 45°, the rock has the minimum tensile strength and the weakest axial deformation resistance.